Feasibility and acceptability of an intervention for enhancing reintegration in adults with experience of homelessness. (11th November 2019) - Sundin, Eva C; Mrowiec, Aleksandra; Bowpitt, Graham; Boatman, Charlotte A; Williams, A J; Sarkar, Mustafa; Baguley, Thom S
Abstract: Background: Service centres for homeless adults are potential settings for implementation of reintegration interventions. This study aimed to evaluate (i) the acceptability of a group-based programme among individuals from the broad population of homeless people and (ii) if a future study of its feasibility and acceptability for re-housed homeless people is warranted. Methods: Recruiting participants and intervention facilitators from partnering service centres was thought to improve recruitment and retention, cost-effectiveness and social interactions compared to professional-led interventions. Seven adults with experience of homelessness (three females, four males, mean age 39 years, range 18–63) were recruited to participate in the intervention. The research protocol comprised completion pre/post of scales [Recovering Quality of Life questionnaire; Working Alliance Inventory-short form revised (WAI-SR)] and focus groups, and WAI-SR and focus groups after sessions 3 and 6. Results: The intervention and research protocols were feasible, with all participants engaging in all sessions, completing all scales and attending all focus groups. The quantitative data demonstrated the feasibility of obtaining practically useful measures of relevant outcomes. In the four focus groups, the intervention received very favourable feedback. Conclusions: This study demonstrated initial feasibility and acceptability of an intervention that places minimal burden on infrastructure and promotes user autonomy. This is an important advance as there is increasing recognition that the challenge of reintegration is as much a psychological and social problem as a housing problem. If effective, this style of intervention may serve as a template for future interventions with similar populations.